2012
DOI: 10.1155/2012/560879
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Continuous Peripheral Nerve Blocks

Abstract: A continuous peripheral nerve block (cPNB) is provided in the hospital and ambulatory setting. The most common use of CPNBs is in the peri- and postoperative period but different indications have been described like the treatment of chronic pain such as cancer-induced pain, complex regional pain syndrome or phantom limb pain. The documented benefits strongly depend on the analgesia quality and include decreasing baseline/dynamic pain, reducing additional analgesic requirements, decrease of postoperative joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 282 publications
(325 reference statements)
2
51
0
1
Order By: Relevance
“…9 A meta-analysis study in 2006 concluded that CPNBs provide superior pain control compared with opioids. 8 The study revealed significantly lower pain scores at multiple time points in patients with CPNBs. 8 The authors concluded that CPNBs can decrease health care expenses by reducing narcotic-related sideeffects.…”
Section: Peripheral Nerve Blockade and Narcotic Consump-tionmentioning
confidence: 77%
See 3 more Smart Citations
“…9 A meta-analysis study in 2006 concluded that CPNBs provide superior pain control compared with opioids. 8 The study revealed significantly lower pain scores at multiple time points in patients with CPNBs. 8 The authors concluded that CPNBs can decrease health care expenses by reducing narcotic-related sideeffects.…”
Section: Peripheral Nerve Blockade and Narcotic Consump-tionmentioning
confidence: 77%
“…Accordingly, continuous PNBs compared to single PNBs were associated with decreased pain ratings on postoperative days 0,1, and 2; decreased overall opioid use; decreased nausea; and higher patient satisfaction scores compared to single-and multiple-injection techniques ( Figure 2). 7,8 Continuous PNBs give physicians the flexibility to adapt to the differing pain thresholds of patients by dropping the volume or concentration of local anesthetic on initial dosing, which decreases the risk of systemic toxicity. Furthermore, by reducing the large initial doses, one is reducing the likelihood of motor and sensory blocks that have been associated with falls and positional injuries.…”
Section: Peripheral Nerve Blockade (Pnb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence is available that the use of regional anesthesia for orthopaedic surgery of the upper extremity conveys desirable advantages, including decreased baseline and dynamic pain, lower consumption of systemic analgesics, decrease of joint inflammation, increase in patient satisfaction, earlier mobilization, and shorter time to discharge readiness [1,14]. However, there is little knowledge on whether incidence of systemic complications, mortality, and resource utilization beyond earlier discharge are affected by the choice of anesthetic technique.…”
Section: Discussionmentioning
confidence: 99%